By the block a pastoral mural in encaustic - Arcipe, Joshua Ianiel C.
Urban development invades our everyday landscape. We constantly confront its uncontrollable changes in the environment, and fail to notice its implications. Our everyday landscapes contain places where we embed them with meanings, histories, and memories, but because of the desire for urbanization, these places have become neglected; some have inevitably vanished.